Revitalizing Local Wisdom in Committing Radicalism in Aceh - Happy Saputra; Mahdalena Nasrun; Muhammad Anzaikhan (INNOVATIO: Journal for Religious Innovation Studies, 2021)
Local wisdom is known as a cultural asset that develops in an area, all policies and customs that play a role in Aceh will become a culture that is respected and appreciated in Aceh. In its development, local wisdom is very influential in protecting people's thoughts, including the seeds of radicalism. The existence of radicalism in Aceh was most evident during the conflict between the Republic of Indonesia and the separatist movement in Aceh. After the peace period of the MOU Helsingki took place, radicalism in Aceh did not occur openly. Only ripples of thought trying to incite from within the disapproval of the current government. You could say, the turmoil arose because of the influence of political color, where the current population of Aceh is quantitatively more inclined to the failed presidential candidate. The problem raised in this study is how to revitalize the values ​​of Aceh's local wisdom which are threatened with fading due to the globalization of foreign cultures. This research design uses qualitative with reference sources based on literature and field studies. The analysis technique is descriptive. The findings of this study are that local wisdom is ideal in countering the existence of radicalism in Aceh through the media meuseumeuraya, tengku authorities, implementing the values ​​of ‘hadih madja’, sub-district da'i programs, and so on. In conclusion, strengthening local wisdom in Aceh is very urgent because the character of the Acehnese people respects traditional values ​​and authority more than the government authority. Abstrak: Kearifan lokal dikenal sebagai aset budaya yang berkembang di suatu daerah, semua kebijakan dan kebiasaan yang memainkan peran keacehan akan menjadi suatu kultur yang dihormati dan dihargai di Aceh. Pada perkembangannya kearifan lokal sangat berpengaruh dalam memproteksi pemikiran masyarakat termasuk bibit-bibit radikalisme. Eksistensi radikalisme di Aceh paling kentara terjadi pada masa konflik antara NKRI dan gerakan sparatis di Aceh. Setelah masa damai MOU Helsingki terjadi, radikalisme di Aceh tidak terjadi secara terbuka. Hanya riak-riak pemikiran yang mencoba menghasut dari dalam tentang ketidaksetujuan terhadap pemerintahan saat ini. Bisa dibilang, gejolak itu muncul karena pengaruh warna politik yang mana saat ini penduduk Aceh secara kuantitas lebih condong pada calon Presiden yang gagal terpilih. Adapun masalah yang diangkat dalam penelitian ini adalah bagaimana merevitalisasikan nilai-nilai kearifan lokal Aceh yang terancam pudar akibat serangan globalisasi budaya luar. Design penelitian ini menggunakan kualitatif dengan sumber referensi berbasis kajian pustaka dan lapangan. Teknik analisis berupa deskriptif. Temuan dari penelitian ini adalah kearifan lokal sangat ideal dalam menangkal eksistensi radikalisme di Aceh melalui media meuseumeuraya, otoritas tengku,implementasi nilai hadih madja, program da’i kecamatan dan lain sebagainya. Kesimpulannya, penguatan kearifan lokal di Aceh sangat urgen karena karakter masyarakat Aceh lebih menghormati nilai dan otoritas adat dibanding otoritas pemerintah. Kata-kata kunci: revitalisasi, kearifan lokal, radikalisme